PENGARUH KOORDINASI, JOB DESCRIPTION (DESKRIPSI PEKERJAAN) DAN TEAMWORK (KERJASAMA TIM) TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA DINAS SOSIAL KOTA BIMA - YULIANA, YULIANA; APRIANTI, KARTIN; IRAWAN, IKBAL (Medikonis, 2024)
Work effectiveness is a balance or optimal approach to achieving goals, abilities and utilization of human energy. This research aims to determine the effect of coordination, job description and teamwork on the work effectiveness of employees at the Bima City Social Service. The sample in this study was 30 ASN with the sampling technique being purposive sampling. Data collection techniques using observation, literature study and questionnaires. The data analysis technique uses multiple linear regression analysis. The results of the research show that coordination, job description and teamwork affect the work effectiveness of employees at the Bima City Social Service simultaneously.